Investigation of the effects of systemic meperidine administration on fascia healing in an experimental rat model - Sensoy,Emine (2020)
Abstract Purpose: To evaluate the effects of meperidine on fascial healing. Methods: Seventy adult male Sprague-Dawley rats divided into 7 groups with 10 rats in each group. One of these groups was determined as the sham group, 3 of the remaining 6 groups as meperidine groups, and 3 as control groups. These were grouped as 1st, 2nd, and 6th weeks. In the anterior abdominal wall of the rat, the skin was detached and a wound model including the peritoneum was created with a median incision. Mice in the meperidine group were injected with meperidine intraperitoneally (IP) 3 × 20 mg/kg meperidine on postoperative days 0, 1 and 2, and 2 × 20 mg/kg meperidine on postoperative days 3, 4, 5, and 6 after surgical intervention. Similar to the control group, an equal volume of saline was administered, corresponding to the doses. After sacrifice, the midline fascia was used for facial tensile strength measurement, and the other for histopathological analysis. Results: When compared, the meperidine and control groups inflammatory cell density was higher in the 1st week (p < 0.05) in the meperidine group, fibroplasia density was found to be higher at the 2nd week in the meperidine group than the control group (p < 0.05) When the tensile strength in the meperidine and control groups were compared, there was no significant difference (p > 0.05) at each of the three weeks. Conclusion: The application of postoperative systemic meperidine affects positively wound healing in the inflammatory stage and fibroplasia without changing the resistance to traction.